Exploring Film Archiving in Malaysia for Public Preservation, Conservation and Access of Visual History - Aliffazraie, Jali; Qistina Donna, Lee Abdullah; Miaw Lee, Teo; Chong Lee, Yow (UNIMAS Publisher, 2022)
The Malaysian film industry has entered the digital industry when all production and national broadcasting companies shifted to digital equipment and facilities. In general, this raises the issue on how to preserve local films from here on out regardless of the video recording method and the question on public accessibility on the materials in the archive. While there are some government institutions tasked with digitising and preserving films (negatives) in Malaysia, little is known about the procedure, protocol, and priority of this development while the public could access little to no information about this matter. Through an in-depth interview with key personnel from National Archives of Malaysia (Arkib Negara), the study investigates the fate of Malaysian films especially the ones produced using film format. Finding indicates that while there is intensive work conducted by Arkib Negara as the official Public Record Service to digitise archived films, priorities are given to film documentaries and governmentrelated news coverage thus setting aside the jewels of Malaysian historical and classical feature films towards uncertain future